Role of nucleases in the isolation of plasmid deoxyribonucleic acid from Pseudomonas cepacia 4G9. - Williams, J A (1980)
Brij 58-cleared lysates of Pseudomonas cepacia 4G9 contain both exonucleolytic and endonucleolytic activities. Endonuclease activity was unaffected by 125 mM ethylenediaminetetraacetic acid, whereas the exonuclease activity was inhibited. In contrast, Sarkosyl NL97 inhibited only the endonuclease. Sodium dodecyl sulfate inhibited all nuclease activity in in vitro assays, but plasmid deoxyribonucleic acid added to P. cepacia 4G9 spheroplasts during sodium dodecyl sulfate lysis was degraded. Irreproducible plasmid isolation from P. cepacia 4G9 may be due to this nucleolytic activity.